Analisis Daya Saing Pariwisata Provinsi Lampung - Derry Putro Adji; Toto Gunarto; Arivina Ratih (Peradaban Journal of Economic and Business, 2022)
The tourism sector is one of the strategic sectors in enhancing local revenue. Revenue from tourism activities have contributed to employment, promote employment in these sub-sectors of tourism. In this study, the tourism object to be studied is Lampung province which is one of the areas that have the potential for high-value tourism. This research measuring the competitiveness of the tourism industry can use variables competitiveness using eight indicators used World tourism organization (WTO), namely, Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Environment Indicator (EI), Technology Advancement Indicator (TAI), Human Resources Indicator (HRI), openness Indicator (OI) and the Social Development Indicator (SDI). This study uses secondary data. The analytical method used in this study is the tourism competitiveness index. The analysis showed that the tourism competitiveness in the eighth indicator shows the value of not being competitive. Sektor Pariwisata merupakan salah satu sektor yang strategis dalam meningkatkan Pendapatan Asli Daerah (PAD). Pendapatan dari kegiatan pariwisata memiliki kontribusi dalam penyerapan tenaga kerja, mendorong kesempatan pada sub-sub sektor pariwisata. Pada Penelitian ini objek pariwisata yang akan diteliti adalah Provinsi Lampung yang merupakan salah satu daerah yang mempunyai potensi pariwisata bernilai jual tinggi. Dalam Penelitian ini pengukuran daya saing industri pariwisata dapat menggunakan variabel daya saing dengan menggunakan delapan indikator yang digunakan World tourism organization (WTO) yaitu, Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Environtment Indicator (EI), Technology Advancement Indicator (TAI), Human Resources Indicator (HRI), Openess Indicator (OI) dan Social Development Indicator (SDI). Penelitian ini menggunakan data sekunder. Metode analisis yang digunakan dalam penelitian ini adalah indeks daya saing pariwisata. Hasil analisis menunjukkan bahwa daya saing pariwisata pada kedelapan indikator variabel menunjukan nilai tidak berdaya saing.